Clustering analysis of high spatial resolution spectra of asteroid (162173) Ryugu from Hayabusa2/NIRS3. (15th September 2022) - Bott, N.; Perna, D.; Deshapriya, J.D.P.; Hasselmann, P.H.; Barucci, M.A.; Domingue, D.L.; Dotto, E.; Kitazato, K.; Matsuoka, M.; Palomba, E.; Usui, T.; Fulchignoni, M.
Abstract: Asteroids, and more globally small bodies, are keys to unravel the origin and the evolution of our Solar system. Remnants of the material which formed planets early on, they captured the composition and the conditions of formation of the latter at that time, since they did not undergo too harsh internal alteration during their lifetimes. The Hayabusa2 spacecraft explored the Cb-type asteroid (162173) Ryugu between June 2018 and November 2019, notably collecting data with its Near-InfraRed Spectrometer (NIRS3) in the 1.8–3.2 ​μm range. We selected five NIRS3 datasets among the ones having the highest spatial resolution on which we applied the G-mode multivariate statistical analysis, in order to spot small heterogeneities at the surface of Ryugu. Both global scale and local scale cases were investigated. With a confidence level of 3 σ, we obtained two classes at global and local scales, while decreasing to 2 σ results in the identification of more classes (five at global scale, four at local scale). Overall, our results are consistent among them and with previous studies. In particular, terrains spectrally redder as well as terrains spectrally bluer than the average surface are newly identified by our analysis. The floors of all main craters at the surface of Ryugu appear redder than their surroundings, and are associated with a probable smaller grain size material. A large depression of the Northern hemisphere may contain bluer heterogeneities likely due to a more packed or/and fresher, subsequently deposited material. Finally, a comparison with data from the Hayabusa2 optical camera ONC-T shows no evident correlation between the spectral properties in the near-infrared and in the visible. Highlights: We selected high-resolution near-infrared spectra of asteroid Ryugu. We applied a multivariate statistical analysis at both global and local scale. Small heterogeneities of composition/alteration are identified. No clear spatial correlation was found with multispectral images of Ryugu.